A Comparative Study in Progressive Aspect of Verbal Affixes of Dangha Tharu Dialect with Nepali and English Languages - Chaudhary, Ram Bahadur; Maharjan, Laxmi Bahadur (Journal of Advanced Academic Research, 2019)
Dangha is one of the dialects of Tharu language. The alternate names of Dangha language are Dangaura, Dangali, Dangauli, Dangora and Dangura. The population of Dangaura language was 500000 in Nepal in 2003. And the number is increasing. Dangaura language is located in Raptizone-Dang, Bheri-Bardiya, Banke and Surkhet districts, Seti zone- Kailali district, Mahakali zone Kanchanpur district, Lumbini zone- Rupandehi and Kapilvastu districts. The status of the variety isthat it is a recognized indigenous national language in Nepal. That is why it is important to study on the verbal affixes of it. The objective of this study is to find out the similarities and differences of verbal affixes of Dangha with Nepali and English languages. The study has applied qualitative method. Questionnaire and interview were used for primary data collection. The researcher used non random and purposive sampling design to select the samples from the population. He used Eugene A. Nida's six principles for verb analysis. -a, -i  and -ti suffixes are used to mark progressive aspect in Dangha dialect. -a and -i suffixes are used to mark point in time whereas -ti suffix is used to mark period of time. In the same way, suffix -ti is used to mark period of time and point in time in future tense. In Nepali language -tai/dai oreko/eki/eka  suffixes are used to indicate progressive aspect while English using suffix to show progressive aspect. Tharu and English have separate progressive aspect marker for point in time or period of time but Nepali progressive marker can be used for both times simultaneously.